1999
DOI: 10.1111/j.1469-8749.1999.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference in ELBW babies is associated with learning difficulties and cognition but not ADHD in the school‐aged child

Abstract: This study examines whether a small head circumference (HC) and low head‐circumference growth velocity (HGV) during the first year of life predict consequences at school age in learning, cognition, and concentration. A total of 124 extremely‐low‐birthweight (ELBW) infants (birthweight 500 to 999 g) born between 1977 and 1986 were eligible for follow‐up at the corrected ages of 4, 8, and 12 months and 2, 4, and 6 years. Infants were categorized as having a small HC (<3% or 3 to 10%) on the basis of the 1990 Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…These studies found positive and significant correlations between HC, SA, IA, brain and parental HC; however, an absence of correlations between brain size, HC and intelligence has been reported in studies of monozygotic twins or in sisters (Tramo et al, 1998;Schoenemann et al, 2000). Other studies have concluded that head size at an early age is a good predictor of later intelligence, learning, cognition and concentration at school age (Botting et al, 1998;Strauss and Dietz, 1998;Stathis et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…These studies found positive and significant correlations between HC, SA, IA, brain and parental HC; however, an absence of correlations between brain size, HC and intelligence has been reported in studies of monozygotic twins or in sisters (Tramo et al, 1998;Schoenemann et al, 2000). Other studies have concluded that head size at an early age is a good predictor of later intelligence, learning, cognition and concentration at school age (Botting et al, 1998;Strauss and Dietz, 1998;Stathis et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Stathis et al 42 found that poor HC growth between birth and 4 months' CA was associated with impaired 6-year cognition in extremely low birth weight infants. Frisk et al 27 showed that cognition was better in the SGA infants with good postnatal HC growth than in SGA infants with a small HC at birth and at 9 months of age.…”
Section: Figurementioning
confidence: 90%
“…In addition, the transplacental transfer of maternal stress hormones, i.e., corticotrophin-releasing factor (CRF) and corticosterone, may affect fetal growth. Moreover, a single course of antenatal betamethasone reduces brain weight in the adult sheep (19) and head diameter in human neonates (2), a finding that has been associated with learning problems in school-age children (20). It is well known that reduced birth size is associated with an increased risk of disease in adulthood (21).…”
Section: Discussionmentioning
confidence: 99%